Factors Affecting Capital Structure in Property and Estate Companies 2019-2022 - Rohim, Cahya Nur; Nurlaela, Siti; Siddi, Purnama (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The purpose of this research is to examine how profitability affects, liquidity, asset structure, and business risk on capital structure. The population of the research consists of property and real estate enterprises listed on the Indonesia Stock Exchange (IDX) in 2019–2022. Quantitative research for use in this sort. In order to choose a sample of 19 businesses for this study, purposeful sampling was employed. The use of multiple linear regression is the method employed in this investigation. The findings from this analysis indicate that the capital structures of property and estate enterprises are affected by factors associated with liquidity and business risk. The capitalization of property and real estate enterprises is unaffected by factors such as profitability and asset structure.